Linear programming approach to coconut-based farming systems intercropping with annuals and animal raising - Colita, June Mary T. (2007)
A linear programming model on coconut-based farming systems intercropped with annual crops was formulated to help farmers in their decision-making. It is a model that maximizes the gross income subject to limited resources such as land, capital labor and other inputs of crops and animals. The model was applied to the coco farmers? that planted annual crop combinations namely: (1) eggplant, sitao or yard-long bean and squash: (2) eggplant, sitao or yard-long bean, tomato and bitter gourd; and (3) corn and banana, and raised animal such as chicken, swine, goat, cattle and carabao. Result of the study shows that under optimal land allocation, the gross income changes linearly with the available capital. The optimal solution did not include allocation of animal raising because the income for raising animas is very little compared to crops. In this case, the input cost of fertilizer and animal draft were not significantly reduced. Thus, it was more profitable to concentrate only in intercropping activities. Labor and land resources were sufficient. Capital was a limiting factor. Availability of more capital through loans can give the farmer a higher income